Truce : Echoes of Art in an Age of Endless Conclusions. - Bonami, Francesco; Foshay-Miller, Bobbie; Friedman, Thomas L.; Grachos, Louis; Phillips, Joann; Schorr, Collier (Santa Fe : SITE Santa Fe, 1997)
Moffatt, Tracey ; Rio Branco, Miguel ; Tayou, Pascale Marthine ; Huang Yong Ping ; Kcho ; Polák, Martin ; Jasanský, Lukás ; Hume, Gary ; Taylor-Wood, Sam ; Toomik, Jaan ; Männikkö, Esko ; Rehberger, Tobias ; Kinoshita, Suchan ; Eliasson, Olafur ; Bartolini, Massimo ; Beecroft, Vanessa ; Cattelan, Maurizio ; Gabellone, Giuseppe ; Hirakawa, Noritoshi ; SubREAL ; Kentridge, William ; Valldosera, Eulàlia ; Krisanamis, Udomsak ; Hanley, Kevin ; Lockhart, Sharon ; Moore, Chris ; Peyton, Elizabeth ; Stingel, Rudolf
biografie
Truce : Echoes of Art in an Age of Endless Conclusions, SITE Santa Fe, July 18 - October 12, 1997
Engels
boek